3, 6-Diamino-7, 8-dihydroisoquinoline-4-carbonitrile derivatives: unexpected facile synthesis, full-color-tunable solid-state emissions and mechanofluorochromic activities. Issue 5 (22nd January 2021) - Zhang, Xinyu; Wang, Dan; Shen, Hao; Wang, Shuxian; Zhou, Yunbing; Lei, Yunxiang; Gao, Wenxia; Liu, Miaochang; Huang, Xiaobo; Wu, Huayue
Abstract : A facile synthesis of novel 3, 6-diamino-7, 8-dihydroisoquinoline-4-carbonitrile derivatives and their solid-state emissions are presented. Abstract : A series of novel 3, 6-diamino-7, 8-dihydroisoquinoline-4-carbonitrile (DDIC) derivatives were prepared from dicyanomethylene-4 H -pyran derivatives and secondary amines by a mechanism of ring-opening and sequential ring-closing reactions. This reaction had the advantages of readily available materials, simple operations, mild reaction conditions, a broad substrate scope, and good yields. The DDIC derivatives displayed solid-state fluorescence with the emission wavelengths covering the whole visible light range, and the solid-state emissions were demonstrated to be ascribed to the twisted molecular conformations and loose stacking modes by crystal structural analyses. Among the compounds, 9aa exhibited a bathochromic mechanofluorochromic (MFC) phenomenon from blue to cyan due to increased molecular conjugation upon grinding, whereas 3aj and 3ka exhibited hypsochromic MFC activities with the color changing from orange to green and red to orange, respectively, because of decreased molecular conjugation, revealing that full-color-tunable emissions could also be realized by mechanofluorochromism. Furthermore, MFC-active molecules can be used in the field of encryption of important image or text information. Additionally, 3ka was demonstrated to emit single-molecular white fluorescence in organic solvents through the regulation of the concentration. The unexpected discovery of the DDIC derivatives provides a new possibility for the design and synthesis of novel isoquinoline-based fluorescent materials with excellent performance in the solid state.